2014
DOI: 10.1142/s021821301460032x
|View full text |Cite
|
Sign up to set email alerts
|

ASAP: An Automatic Algorithm Selection Approach for Planning

Abstract: Despite the advances made in the last decade in automated planning, no planner outperforms all the others in every known benchmark domain. This observation motivates the idea of selecting different planning algorithms for different domains. Moreover, the planners' performances are affected by the structure of the search space, which depends on the encoding of the considered domain. In many domains, the performance of a planner can be improved by exploiting additional knowledge, for instance, in the form of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…In planning, some objects might be symmetric, which can be exploited for avoiding alternatives concerning one object that has been already tried with the object's symmetric "twin." 38 A recent work, which is, to some extent, similar to inner entanglements, proposes a method to learn "bad" causal links in order to generate plans of better quality. This approach has been recently extended for cost-optimal planning.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In planning, some objects might be symmetric, which can be exploited for avoiding alternatives concerning one object that has been already tried with the object's symmetric "twin." 38 A recent work, which is, to some extent, similar to inner entanglements, proposes a method to learn "bad" causal links in order to generate plans of better quality. This approach has been recently extended for cost-optimal planning.…”
Section: Related Workmentioning
confidence: 99%
“…Pruning techniques are often an inseparable part of advanced planning engines. 38 Exploiting a natural property of inner entanglements, ie, exclusivity of predicate achievement or requirement, has been also used for generating macros. We demonstrated that inner entanglements can often significantly improve their performance.…”
Section: Relationship To Other Pruning or Problem Reformulation Technmentioning
confidence: 99%
See 2 more Smart Citations
“…There are planner portfolio configuration systems mainly designed to generate domain-specific planners, such as PbP and ASAP [5,6], as well as a range of domain-independent portfolio planners. Among the latter, we can identify two main classes: static portfolios, which run the same schedule of planners on every given problem instance, and portfolios based on per-instance planner schedules.…”
Section: Introductionmentioning
confidence: 99%